1973
DOI: 10.1073/pnas.70.9.2678
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Polypeptide Initiation In Vitro After Protein Synthesis Inhibition In Vivo in HeLa Cells

Abstract: Crude cytoplasmic extracts prepared from HeLa cells actively incorporate amino acids but show little initiation of new peptides (as seen by labeling of N-terminal amino acids). In contrast, extracts prepared from cells subjected to prior inhibition of protein synthesis show a significant amount of polypeptide initiation indicated by formation of peptides with radioactive N-terminal methionine. The same result was obtained whether prior inhibition occurred with cycloheximide or by starvation for an essential am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1974
1974
1998
1998

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…More than 20 years ago, Reichman and Penman identified a factor, termed an activator, which stimulates translational initiation (37). They demonstrated that this activator is an RNA with a half-life of about 1 h, which is approximately the short lifetime of flAlu RNA (6,16).…”
Section: Discussionmentioning
confidence: 99%
“…More than 20 years ago, Reichman and Penman identified a factor, termed an activator, which stimulates translational initiation (37). They demonstrated that this activator is an RNA with a half-life of about 1 h, which is approximately the short lifetime of flAlu RNA (6,16).…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence from both in vivo studies and in vitro ability to initiate protein synthesis has indicated that some metabolic activity involving RNA is necessary to maintain proper initiation rates in HeLa cells. This process is inhibited by actinomycin (2,10,11). When this phenomenon was examined in detail in in vivo experiments, it was found that the actinomycin concentration required for half-maximum effect was 0.1-0.2 ,g/ml.…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of experimentation suggest that an important site of control is the process of initiation (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In exponentially growing HeLa cells, it has been possible to induce enhanced rates of initiation in vivo (2,10) by exposing cells to a period of decreased protein synthesis caused by elevated temperature, treatment with cycloheximide, or starvation for an essential amino acid.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier the involvement of a small RNA in protein biosynthesis was postulated by several authors (2)(3)(4). Lowering of the level of this RNA might be responsible for the observed decline in protein synthesis after the administration of actinomycin D (3).…”
mentioning
confidence: 99%